2023
DOI: 10.2196/42967
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mobile App to Monitor the Effectiveness of a Hydrolyzed Cartilage Matrix Supplement on Joint Discomfort: Real-World Study

Abstract: Background Joint discomfort is a widespread and growing problem in active adults. The rising interest in preventative nutrition has increased the demand for supplements reducing joint discomfort. Protocols assessing the effect of a nutritional intervention on health commonly involve a series of face-to-face meetings between participants and study staff that can weigh on resources, participant availabilities, and even increase dropout rates. Digital tools are increasingly added to protocols to facil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Similarly, joint functionality seemed to be improved in the current investigation as participants experienced reduced restrictions when squatting. Although results coming from studies in a population with a wider age range confirmed the findings [43][44][45], some investigations could not report improvements in joint pain and functionality [59,60].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, joint functionality seemed to be improved in the current investigation as participants experienced reduced restrictions when squatting. Although results coming from studies in a population with a wider age range confirmed the findings [43][44][45], some investigations could not report improvements in joint pain and functionality [59,60].…”
Section: Discussionmentioning
confidence: 90%
“…However, most of these trials included participants with osteoarthritis [ 33 , 34 , 35 , 37 , 38 , 39 , 40 ]. Studies focusing on functional joint pain examined exclusively exercise-induced joint pain in both younger participants [ 36 , 41 , 42 ] and a study population with a wider age range (>18) [ 43 , 44 , 45 ]. It has previously been described that activity-induced joint pain is related to former injuries, anatomical deformities, long-term stress and high impact on the joint in combination with inadequate regeneration phases, wrong techniques or movement sequences [ 41 , 42 , 46 ].…”
Section: Introductionmentioning
confidence: 99%